(untitled) (Contemporary Journal of Social Science Review, 2025)
Pakistan is a multi-sectarian Islamic society where different jurisprudential, intellectual and religious interpretations have existed for centuries. Although this diversity is in essence a manifestation of intellectual breadth and scholarly wealth, However, in recent decades, due to certain social, political and historical factors, this same diversity has also become a cause of sectarian tension and intolerance. In this context, the promotion of inter-sectarian harmony has become an indispensable necessity for the peace, stability and social progress of Pakistani society. The main objective of this research is to identify the principles present in the Holy Quran, the Sunnah of the Prophet (PBUH) and the Islamic intellectual tradition that provide the basis for inter-sectarian harmony, tolerance and mutual respect, and to clarify how these teachings can be effectively implemented in the Pakistani social context. The research has studied the basic Islamic sources through Textual Analysis, while under the Analytical Method, the sectarian diversity existing in Pakistan and the social attitudes related to it have been critically examined. The present paper will attempt to understand this important issue analytically in the light of Islamic teachings. The study reveals that Islamic teachings recognize differences of opinion as a natural thing but advise to keep these differences within the scope of dialogue, justice and good morals instead of conflict. The Holy Quran emphasizes the principles of unity of the Ummah, moderation, and human dignity, while the life of the Prophet Muhammad (PBUH) provides practical examples of peaceful coexistence with different tribes and intellectual groups. The main findings of the research show that the major causes of sectarian tension in Pakistan are deviations from religious teachings, partial interpretations and unscientific emotionalism, and not the original principles of Islam. This research is important in that it places the issue of interfaith harmony in an intellectual and religious context rather than considering it as a mere social or political issue. The paper concludes that if Islamic teachings, in their true spirit, are made part of the educational curriculum, sermons, media, and social dialogue, the path to promoting sustainable interfaith harmony in Pakistani society can be paved.